A Laser-Based Noncontact Vibration Technique for Health Monitoring of Structural Cables: Background, Success, and New Developments - Mehrabi, Armin B.; Farhangdoust, Saman (Advances in acoustics and vibration, 2018)
Structural cables are susceptible to the effects of high stress concentrations, corrosion, and wind-induced and other vibrations. Cables are normally the most critical elements in a cable-supported structure and their well-being is very important in the health of the structure. The laser-based vibration technique discussed in this paper is a means for health monitoring of cables and therefore the entire cable-supported structure. This technique uses a noncontact remote sensing laser vibrometer for collecting cable vibration data from distances of up to several hundreds of feet and determines its dynamic characteristics including vibration frequencies and damping ratios. A formulation specifically developed for structural cables capable of accounting for important cable parameters is then used to calculate the cable force. Estimated forces in the cables are compared to previously measured forces or designer’s prediction to detect patterns associated with damage to the cable itself and/or changes to the structure elsewhere. The estimated damping ratios are also compared against predefined criteria to infer about susceptibility against wind-induced vibrations and other vibrations. The technique provides rapid, effective, and accurate means for health monitoring of cable-supported structures. It determines the locations and elements with potential damage and the need for detailed and hands on inspection. To date, the technique has been used successfully for evaluation of twenty-five major bridges in the US and abroad. Though originally devised for condition assessment of stay cables, it has been developed further to include a variety of systems and conditions among them structural hanger ropes in suspension, truss, and arch supported bridges, ungrouted stay cables, cables with cross-ties, and external posttensioning tendons in segmental bridge construction. It has also found a valuable place in construction-phase activities for verification of forces in tension elements with minimal efforts. Future endeavors for automation and aerial delivery are being considered for this technique.